Interferon alpha inducible protein 6 is a negative regulator of innate immune responses by modulating RIG-I activation - Villamayor, Laura; Rivero, Vanessa; López-García, Darío; Topham, David J.; Martínez-Sobrido, Luis; Nogales, Aitor; DeDiego, Marta L. (Frontiers in Immunology, 2023)
Interferons (IFNs), IFN-stimulated genes (ISGs), and inflammatory cytokines mediate innate immune responses, and are essential to establish an antiviral response. Within the innate immune responses, retinoic acid-inducible gene I (RIG-I) is a key sensor of virus infections, mediating the transcriptional induction of IFNs and inflammatory proteins. Nevertheless, since excessive responses could be detrimental to the host, these responses need to be tightly regulated. In this work, we describe, for the first time, how knocking-down or knocking-out the expression of IFN alpha-inducible protein 6 (IFI6) increases IFN, ISG, and pro-inflammatory cytokine expression after the infections with Influenza A Virus (IAV), Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), and Sendai Virus (SeV), or poly(I:C) transfection. We also show how overexpression of IFI6 produces the opposite effect, in vitro and in vivo, indicating that IFI6 negatively modulates the induction of innate immune responses. Knocking-out or knocking-down the expression of IFI6 diminishes the production of infectious IAV and SARS-CoV-2, most likely because of its effect on antiviral responses. Importantly, we report a novel interaction of IFI6 with RIG-I, most likely mediated through binding to RNA, that affects RIG-I activation, providing a molecular mechanism for the effect of IFI6 on negatively regulating innate immunity. Remarkably, these new functions of IFI6 could be targeted to treat diseases associated with an exacerbated induction of innate immune responses and to combat viral infections, such as IAV and SARS-CoV-2.